MCTS 70-642 exam cram : Windows server 2008 network infrastructure, configuring - Regan, Patrick E. (Que Pub., 2008)
Covers the critical information you need to know to score higher on your 70-642 Exam! Configure IPv4 and IPv6 addressing and services Work efficiently with Dynamic Host Configuration Protocol (DHCP) Manage advanced server features such as Server Core and Hyper-V Configure routing, including RIP and OSPF-based routing Secure networks with firewalls, policies, IPSec, authentication, Network Access Protection, and the Baseline Security Analyzer Configure DNS servers, zones, records, replication, and client computer name resolution Manage remote access, from NAT and VPNs to RRAS and RADIUS services Implement secure wireless access using SSID, WEP, WPA, WPA2, and group policies Configure file and print services, including disk quotas, DFS, and EFS Establish efficient automated backups and manage restores Monitor network performance and events Streamline updates with Windows Server Update Services (WSUS) CD Features MeasureUp Practice Questions! Detailed explanations of correct and incorrect answers Multiple test modes Random questions and order of answers Coverage of each 70-642 Exam objective.